Study guides

Q: What is the answer to negative 6x plus 9 equals 9-3x?

Write your answer...

Submit

Related questions

Not necessarily.

4x + 7 = 6x -7 14=2x so x = 7 (plus a negative # is simply - that number)

negative one and a half

x=-3

y = -6x + 3 Multiply the slope by the negative reciprocal y = 1/6x + 3

(9,6)

6x plus 3 equals 8x plus 14 when solved mathematically is equal to x = -5.5.

-6x

6x+x = 7x

The quadratic expression x2+6x+8 when factorised equals (x+2)(x+4)

It is: 3x2+6x-11 = 0

6x plus 3y minus 2x plus 5y equals 4x plus 8y.

x=10

5x + x - 6x + 2x = 2x

6x plus 3 equals to 8x plus 14 would lead to x = - 5.5.

The coefficient of x2 is -3 which is negative. Therefore the curve is downward opening.

(9,2)

6x

y=(6x-5)/3

7x + 2 = 6x + 2 if and only x = 0.

74

144

6x + 34 = 4x +284 6x - 4x = 284 - 34 2x = 250 x = 125

16x+9 without the rest of the equation, what this equals, I can't solve

6x+4=52 6x=48 x=8